Someday Angeline - Sachar, Louis 1954- (New York HarperTrophy, 1983)
As an eight-year-old genius in the sixth grade, Angeline is not too popular, but she tries to adjust to being different.
Keywords: Self-acceptance -- Fiction; Schools -- Fiction